2018
DOI: 10.1016/j.jaci.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-cell dysfunction induces autoantibodies to bullous pemphigoid antigens in mice and human subjects

Abstract: Dysregulation of Treg cells generates autoantibodies to COL17 and BP230 in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 60 publications
2
65
0
2
Order By: Relevance
“… and Muramatsu et al. also successfully illuminated the pathogenic function of anti‐BP230 IgG autoantibodies. They demonstrated that in scurfy mice whose regulatory T cells (Treg) were defective ( Foxp 3 mutation), there was spontaneous production of IgG1 autoantibodies to BP230.…”
Section: In Vivo Studies Of Autoantibodies Against Bp230mentioning
confidence: 99%
See 1 more Smart Citation
“… and Muramatsu et al. also successfully illuminated the pathogenic function of anti‐BP230 IgG autoantibodies. They demonstrated that in scurfy mice whose regulatory T cells (Treg) were defective ( Foxp 3 mutation), there was spontaneous production of IgG1 autoantibodies to BP230.…”
Section: In Vivo Studies Of Autoantibodies Against Bp230mentioning
confidence: 99%
“…Recently, Haeberle et al. and Muramatsu et al. also successfully illuminated the pathogenic function of anti‐BP230 IgG autoantibodies.…”
Section: In Vivo Studies Of Autoantibodies Against Bp230mentioning
confidence: 99%
“…2,5 The interval between start of ICIs and BP onset was highly variable with a median of 6 months, as in our cases. 7 Hence, Tregs blockade may result in both autoreactive cellular and humoral response to the same antigenic targets of the epidermal and epithelial BMZ. 5 Immune checkpoint inhibitor therapy with anti-programmed death-1/ programmed death-ligand 1 results in a breakdown of tolerance, reduces activity of regulatory T cells (Tregs) and activates B cells and autoreactive T cells.…”
Section: Mucous Membrane Pemphigoid and Lichenoid Reactions After Immmentioning
confidence: 99%
“…Bullous pemphigoid (BP) is an organ‐specific autoimmune disease of the skin, characterized and caused by autoantibodies targeting BP180 and/or BP230 . In the ‘classical’ and name‐giving variant, BP patients present with blisters on inflamed skin.…”
mentioning
confidence: 99%
“…Based on these findings, and on experimental data, inflammation and blistering in BP has been thought to be mediated by BP180 autoantibodies only. However, the pathogenicity of anti‐BP230 autoantibodies has recently been well documented …”
mentioning
confidence: 99%